2022
DOI: 10.1155/2022/7135125
|View full text |Cite
|
Sign up to set email alerts
|

Application and Efficacy of Melatonin Elastic Liposomes in Photoaging Mice

Abstract: Transdermal drug delivery system is a preferable choice to overcome the low bioavailability of oral medication. Elastic liposomes have shown great effectiveness for percutaneous transport of melatonin (MLT). In this study, the elastic liposomes loaded with MLT were prepared using thin-film dispersion method and optimized through the central composite design (CCD) approach. The physicochemical properties and skin permeation against UV-induced skin photoaging efficacy of the developed MLT-ELs were assessed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Permeation studies revealed a 1.5-fold improvement in the penetration of elastic liposomes compared to simple liposomes. Increased skin hydration, coupled with the reinforcement of collagen fibers, indicated the restoration of skin elasticity upon treatment with MLT-EL in photoaging experiments [331].…”
Section: Melatoninmentioning
confidence: 92%
“…Permeation studies revealed a 1.5-fold improvement in the penetration of elastic liposomes compared to simple liposomes. Increased skin hydration, coupled with the reinforcement of collagen fibers, indicated the restoration of skin elasticity upon treatment with MLT-EL in photoaging experiments [331].…”
Section: Melatoninmentioning
confidence: 92%
“…The prepared elastic liposomes crossed the UV-induced photoaged skin layers of the female Kunming mice model more efficiently than liposomes utilized conventionally, improving dermal hydration and elasticity by maintaining collagen and fibers of derma during in vivo evaluation. Hence, it could be employed successfully for the future application for encapsulation of poorly soluble and low bioavailable therapeutic agents for treating skin diseases . Since the term “liposome” has a broad definition that encompasses several types of vesicles with typical sizes up to several micrometers, nanoliposomes have been referred to as nanoscale bilayer lipid vesicles .…”
Section: Vesicular Drug Delivery Systemsmentioning
confidence: 99%
“…Hence, it could be employed successfully for the future application for encapsulation of poorly soluble and low bioavailable therapeutic agents for treating skin diseases. 176 Since the term “liposome” has a broad definition that encompasses several types of vesicles with typical sizes up to several micrometers, nanoliposomes have been referred to as nanoscale bilayer lipid vesicles. 177 Clove essential oil (CEO) and tea tree oil (TTO) were combined in varied concentrations and put into multicompositional nanoliposomes.…”
Section: Vesicular Drug Delivery Systemsmentioning
confidence: 99%
“…Egrilmez et al (18) HDFs from 10 fe-males aged 20-40 years old with Fitz-patrick type III and IV -1 μM melatonin -0.1 J/cm 2 of UVB (311 ± 5 nm) for 6 s Melatonin inhibits UVBinduced oxidative/ nitrosative stress damage, downregulates UV-in-duced activation of EGFR and the c-Jun N-terminal kinase (JNK)/activator protein-1 (AP-1) signaling pathway, decreases UVB-induced activities of matrix metalloproteinase (MMP)-1 and MMP-3, increases tissue inhibitor of metalloproteinase (TIMP)-1 and procollagen type I C-peptide (PIP-C). Hou et al (19) 30 Kunming female mice (35 ± 5 g) -300 µl melatonin elastic liposomes (MLT-ELs) -2 hours irradiation with UV lamp (223 nm) 30 cm away, for 10 weeks MLT-ELs ameliorate the skin elasticity, enhance the skin hydration level, and preserve the integrity of dermal collagen and elastic fibers.…”
Section: Melatonin-based Cream For 12 Weeksmentioning
confidence: 99%